Assessment of male patients’ average glandular dose during mammography procedure - Sulieman, Abdelmoneim; Salah, Hassan; Rabbaa, Mohammad; Abuljoud, Mohammad; Alkhorayef, M.; Tahir, Dahlang; Tamam, N.; Saeed, Mohammed K.; Bradley, D.A. * (Elsevier, 2023)
Breast cancer is a common malignancy for females (25% of female cancers) and also has low incidence in males. It was estimated that 1% of all breast malignancies occur in males with mortality rate about 20%, with annual increase in incidence. Risk factors include age, family history, exposure to ionizing radiation and high estrogen and low of androgens hormones level. Diagnosis and screening are challenging due to limiting effectiveness of breast cancer screening. Therefore, patients may expose to ionizing radiation that may contribute in breast cancer incidence in males. In literature, limited studies were published regarding radiation exposure for males during mammography. The objective of this research is to quantify patient doses during male mammogram and to estimate the projected radiogenic risk during the procedure. In total, 42 male patients were undergone mammogram for breast cancer diagnosis during two consecutive years. The mean and range of patient age (years) is 45 (23–80). The mean and standard deviation (SD) of the peak tube potential and tube current time product are 28.64 ± 2. and 149 ± 35.1, respectively. The mean, and range of patients’ entrance surface air kerma (ESAK, mGy) per single breast procedure was 5.3 (0.47–27.5). Male patient’s received comparable radiation dose per mammogram compared to female procedures. With increasing incidence of male breast cancer, proper guidelines are necessary for the mammographic procedure are necessary to reduce unnecessary radiation doses and radiogenic risk.